Computational Techniques for Autonomous Microgrid Load Flow Analysis. (11th May 2014) - Kirthiga, M. Venkata; Daniel, S. Arul
Abstract : This paper attempts at developing simple, efficient, and fast converging load flow analysis techniques tailored to autonomous microgrids. Two modified backward forward sweep techniques have been developed in this work where the largest generator is chosen as slack generator, in the first method and all generator buses are modeled as slack buses in the second method. The second method incorporates the concept of distributed slack bus to update the real and reactive power generations in the microgrid. This paper has details on the development of these two methodologies and the efficacy of these methods is compared with the conventional Newton Raphson load flow method. The standard 33-bus distribution system has been transformed into an autonomous microgrid and used for evaluation of the proposed load flow methodologies. Matlab coding has been developed for validating the results.